PENGEMBANGAN BAHAN AJAR RADEC BERKEARIFAN LOKAL TABOT BENGKULU BERBANTU DASHBOARD INFOGRAFIS UNTUK MENULIS DESKRIPSI SISWA KELAS IV SEKOLAH DASAR - Afrilyani, Wulan; Muktadir, Abdul; Gumono; Agusdianita, Neza; Juarsa, Osa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low descriptive-writing skills of fourth-grade students and the limited availability of teaching materials integrating an active learning model with local cultural content. This research aimed to describe the characteristics, feasibility, user responses, and profile of students' descriptive-writing skills after using Read, Answer, Discuss, Explain, Create (RADEC) teaching materials based on the local wisdom of Tabot Bengkulu, supported by an infographic dashboard. The study used the Research and Development (R&D) method with the ADDIE model, covering the analysis, design, development, implementation, and evaluation stages. Participants consisted of six validators, one fourth-grade teacher, and 18 fourth-grade students of SD Negeri 60 Bengkulu Tengah. Data were collected through interviews, observation, expert validation sheets, teacher and student response questionnaires, and descriptive-writing assessments, then analyzed using Aiken's V and inter-rater reliability formulas. Results showed that the developed material integrates the RADEC syntax, Tabot Bengkulu local wisdom, and an infographic dashboard as the main visual medium. The material was declared highly valid, with Aiken's V scores of 0.89 for material, 0.873 for language, and 0.92 for graphic design. Teacher and student responses were very positive, reaching 100% and 98% respectively. The average descriptive-writing score of the effectiveness class reached 84.0, higher than the trial class score of 67.4, a gain of 16.6 points. These findings indicate that the RADEC teaching material based on Tabot Bengkulu local wisdom and supported by an infographic dashboard is valid, practical, and effective for improving descriptive writing skills while supporting deep learning among elementary school students.